Bases da terapia celular magnética com endotélio corneal: cultura e magnetização celular - Grottone, Gustavo Teixeira [UNIFESP] (2014)
Purpose: To evaluate the foundations of human corneal endothelial cell therapy with magnetic and non-magnetic cells. Methods: Thirty six corneas donated by eye bank and twelve rabbits were used in this study. Human corneal endothelial cells previously cultured in vitro were divided in two groups: exposed or non-exposed to magnetic nanoparticles. Those cells were used as an attempt to regenerate our ex-vivo host corneas. Cell colonies were tracked after 7 days using an scanning laser ophthalmoscope with a excitation light of 488 nm. The rabbits were divided into two groups according to the treatment used: ABRASION or DESCEMET. After 30 days, corneal central thickness and edema of both grupos were recorded. Those corneas that presented clinical signs of bullous keratopathy underwent endothelial cell therapy. Results: Human corneal endothelial cells showed no toxicity when exposed to the studied nanoparticle(p=0.507). Endothelial cell failure experimental models were different when considering central corneal thickness after 30 days(p<0.001).Indeed, the group which expressed greater edema, also showed extensive fibrotic tissue at posterior corneal surface, thus, preventing the use of this model in our study. Both, non-magnetic and magnetic cells were found attached to posterior surface of corneas after 7 days of ex-vivo cultures. Conclusions: Human corneal endothelial cells from magnetic and non-magnetic groups attached to corneal posterior surface on ex-vivo hosts.